Antibiotics in intensive egg production: Food Safety tools to ensure regulatory compliance - Érica Lima; M Beatriz Oliveira; Andreia Freitas (Food Chemistry Advances, 2023)
Egg production systems use antibiotics to treat and prevent the spread of diseases. Antibiotics remain in the animal's body in their original or metabolized form and they can remain in different organs and eggs. The constant consumption of trace doses of antibiotics through food is a serious public health concern, as it can potentiate antimicrobial resistance (AMR). To protect public health, the European Commission defined recommendations to reduce and control the use of those substances in farm animals. Detection and quantification methods using liquid chromatography-mass spectrometry (LC-MS) allow checking whether the antibiotic content meets the maximum residue limit (MRL) or if prohibited antibiotics are present. The egg is a complex matrix and the antibiotic extraction from this matrix is a challenger step present in the detection and quantification process of these molecules. Therefore, this review presents an overview of methods for extracting antibiotics from eggs, and serves as a baseline for new methods able to extract as many antibiotics as possible, coupled with an accurate detection strategy. According to the information collected, the most common extraction solutions were formic acid with acetonitrile, water, and solutions containing ethylenediaminetetraacetic acid (EDTA). Purification via solid-phase extraction (SPE) is also common. Among the detection methods, chromatography coupled to quadrupole mass detectors with positive electrospray ionization using octadecylsilane (C18) as the stationary phase is the most common approach. The developments achieved to optimized analytical strategies are in line with the needed tools to guarantee food safety monitoring and the fulfillment of regulations in place.